Emergency Warning After the Constitutional Court Decision on the 2024 Regional Elections: Maintaining Political Stability in the Hadis Review - Maulida, Nur Rikha; Anwar, Latifah (Universitas Ibn Khaldun, 2025)
This research was motivated by the reality of the emergence of emergency warning posts on social media following the Constitutional Court's decision regarding the 2024 Regional Head Election (Pilkada), which sparked public concern about political instability in Indonesia. The aim of this research is to discuss the pattern of political stability regarding emergency warnings after the 2024 Regional Election Constitutional Court decision and review it based on the hadith of the Prophet. This research uses library research with a descriptive-analytical method related to literature such as scientific articles, popular articles, books, significant prophetic hadith with discussion. The formal objects of this research are emergency warnings on social media and the Constitutional Court's decision regarding the 2024 regional elections. Meanwhile, the material objects of this research are emergency warnings and hadith related to political stability. The discussion in this research shows that political stability is the responsibility of the government and citizens. The conclusion of this research is that maintaining political stability is highly recommended by Allah and His Messenger. By implementing good leadership, the country's political system will be stable and its people will receive many benefits.